Heresy in the Heartland : The Controversy at The University of Dayton, 1960-67 - Brown, Mary Jude, 1950- (Book collections on Project MUSE., 2022)
"Heresy in the Heartland is a narrative case study of the 'Heresy' Affair at the University of Dayton, a series of events predominantly in the philosophy department precipitated by tensions between the Thomists and proponents of new philosophies. It reached crisis stage in fall 1966 when a lay assistant professor asked the archbishop to conduct an investigation into the "erroneous teachings" of four lay faculty members. The story is told in chronological order by the participants in the controversy - faculty, administrators, students and clergy - using the words of those involved. Heresy in the Heartland concludes with a synopsis of what happened at the University of Dayton and draws some lessons for the future of Catholic higher education"--